Women's poetry - Gill, Jo, 1965- (Edinburgh critical guides to literature., 2007)
This guide examines the production and reception of poetry by a range of women writers - predominantly although not exclusively writing in English - from Sappho through Anne Bradstreet and Emily Bronte to Sylvia Plath, Eavan Boland and Susan Howe. Women's Poetry offers a thoroughgoing thematic study of key texts, poets and issues, analysing commonalities and differences across diverse writers, periods, and forms. The book is alert, throughout, to the diversity of women's poetry. Close readings of selected texts are combined with a discussion of key theories and critical practices, and students are encouraged to think about women's poetry in the light of debates about race, class, ethnicity, sexuality, and regional and national identity. The book opens with a chronology followed by a comprehensive Introduction which outlines various approaches to reading women's poetry. Seven chapters follow, and a Conclusion and section of useful resources close the book. Key Features Wide-ranging and flexible in scope, giving detailed consideration to widely-taught poets, texts, periods and issues Introduces themes, questions and perspectives applicable to the work of other less familiar writers Encourages informed discussion of the difficulties of defining a discrete genre of 'women's poetry' Offers valuable introductory and supplementary guidance for students Discusses in detail poems by Margaret Cavendish, Anne Bradstreet, Sara Coleridge, Christina Rossetti, Emily Dickinson, Edith Sitwell, Amy Lowell, Sylvia Plath, Ruth Fainlight, Grace Nicholls, Eavan Boland, Kathleen Jamie, Jackie Kay and Carol Ann Duffy.